Mediating Roles of Gratitude and Social Support in the Relation Between Survivor Guilt and Posttraumatic Stress Disorder, Posttraumatic Growth Among Adolescents After the Ya’an Earthquake - Wang, Wenchao; Wu, Xinchun; Tian, Yuxin (Frontiers in Psychology, 2018)
Objective: This study aims to examine the mediating roles of gratitude and social support in the relationship between survivor guilt and posttraumatic stress disorder (PTSD) as well as the relationship between survivor guilt and posttraumatic growth (PTG). Methods: The current study used self-report questionnaires to investigate 706 adolescent survivors of Lushan county three and a half years after the Ya’an earthquake. The structural equation model was used to evaluate the relations between survivor guilt, gratitude and social support in PTSD and PTG. Results: The results indicated that survivor guilt had a positive effect on both PTSD and PTG. Gratitude partly mediated the relation between survivor guilt and both PTSD and PTG; social support partly mediated the relation between survivor guilt and PTG but not PTSD as well as the relation between gratitude and PTG. Conclusion: Survivor guilt has a double-edged sword effect. Survivor guilt affects PTSD and PTG through gratitude, and it could affect PTG but not PTSD through social support. Gratitude decreases PTSD and increases PTG, whereas social support only increases PTG.